Reformasi Sistem Pendidikan Almajiri di Nigeria Melalui Paradigma Maqashid Al-Shari’ah - Lateef, Abiola Muideen; Tijani, Abdul-Lateef Aremu; Ahmad, Muhammad Bashir (Fahima, 2024)
The Almajiri phenomenon is one of the pandemic matters affecting Muslims in the North, specifically Nigeria as a nation. It depicts a condition whereby children of school age, ostensibly enrolled to study under Mallams, roam about the streets in tattered clothes, begging, scavenging, and doing all sorts of odd jobs. While Islam places a high premium on education, emerging issues about The Almajiri system of education have heightened the need to re-examine the concept from the perspective of the essence, purpose, goal, and objective of Islamic law (Maqasid al-Shari’ah). To this extent, the practice of the Almajiri system of education as obtainable in Nigeria should be subjected to the balance of Maqasid as-Shari’ah to ascertain its acceptability and fecundity. This paper therefore attempts to assess and appraise the Almajiri educational system in Nigeria to reform its operation and recommend steps towards attaining the overall educational goals of Islam as enshrined in the Shari’ah. The researcher adopts both historical and narrative research methods in the work. This article finds a strong correlation between the Almajiri system of education and Maqasid as-Shari’ah.  The research concludes that there is a dire need for Nigerian Muslims to adopt the Maqasid as-Shari’ah as the guiding principle for the reformation and operation of the Almajiri educational system, particularly in the northern part of the country.